Pengaruh Kesulitan Keuangan terhadap Manajemen Laba dengan Internal Audit sebagai Variabel Pemoderasi pada Perusahaan Non-Finansial yang Terdaftar di Bursa Efek Indonesia Periode 2013-2019 - Devi Silviana; Elfina Astrella Sambuaga (Research Center and Case Clearing House PPM School of Management, 2022)
This study aims to provide empirical evidence regarding the effect of financial distress towards earnings management and the role internal audit as a moderating variable. This study uses all non-financial companies listed in Indonesia Stock Exchange during 2013-2019, totalled 1,442 observations. The results show that Distress1 proxied by z-score can reduce accrual and real earnings management practices, while D_Distress2 proxied by net working capital can increase accrual earnings management but reduce real earnings management practices. In addition, internal audit does not have a moderating role in weakening the effect of financial distress on earnings management but can reduce accrual and real earnings management practices.